Enhancing Hots and Entrepreneurial Competencies Through Avnet Academic Applications in English Learning - Siahaan, Mungkap Mangapul; Sijabat, Apriani; Samosir, Hottua; Purba, Rudiarman; Terizla, Rizky Fredrin (Aptisi Transactions On Technopreneurship (ATT), 2025)
The development of e-learning in the independent curriculum for Senior High School Students (SHS) aims to foster critical reasoning, collaboration, creativity, and inspire independent learning for each student. In accordance with the results of the research data taken from the learning interaction in class tenth of the SHS in Humbahas Regency, Avnet Academic (A2) is able to develop autonomous learning, talents, attitudes, and academic competencies. They also were able to organize their own learning management. The research result showed that they improved their self-quality and the educational quality. The series of the research patterns analyzed all interactions within the A2 which was characterized by HOTS. A2 applied to the grade ten students. The students were randomly selected as many as 500 participants. Using the A2 in learning interactions required mobile devices, Pc Computers and Laptops as access entry to serve with the various learning activity features. The features are integrated with YouTube, Google, Learning ID, school website and other internet-connected applications. The research used mixed methods as: data processing using the Excell, Amos and NVIVO applications. Research showed that t_count = 33.5 is much greater than t_table = 1.96 so it can be concluded that the A2 is not only trains English language skills but can also be integrated with other subjects so that cognitive, affective and psychomotor elements can be innovated, collaborated, evaluated and developed sustainably so as to produce students with HOTS character.